Pengaruh Profesionalisme Pegawai terhadap Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bone Bolango - Meydina Saufika Lukum; Sri Yulianty Mozin; Rustam Tohopi (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2026)
Public service quality is an essential element of responsive governance. However, the Department of Population and Civil Registration of Bone Bolango Regency still faces challenges related to service completion time and compliance with operational procedures due to the suboptimal responsiveness of its employees. This study aims to analyze the effect of employee professionalism on public service quality at the institution. A quantitative correlational approach was employed, involving 43 employees selected through saturated sampling (census). Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and simple linear regression. The results reveal that employee professionalism has a positive and significant influence on public service quality. Professionalism reflected in creativity, innovation, and responsiveness contributes 69.80% to the performance of population administration services. These findings indicate the importance of strengthening human resource development strategies within the institution. Efforts such as interpersonal communication training, enforcement of discipline in accordance with Standard Operating Procedures (SOP), and acceleration of digital-based service adaptation are necessary to improve public trust and community satisfaction in a sustainable manner.